Optimal Variable Frequency Soft Switching for Interleaved Grid Tied Inverters in Electric Vehicle Charging Applications - Youssef A. Fahmy; Matthew Jahnes; Matthias Preindl (Energies)
Synchronized variable frequency soft-switching is analyzed and implemented in a 3-phase bidirectional grid-tied inverter. The common-mode connected topology and control allow for independent analysis of a single phase leg before six are combined into two interleaved, 3-phase inverters. Effective operation is enabled by discretizing the variable switching frequencies before synchronizing them with a control signal. The resulting inverter can operate at any power factor at power levels up to 50 kVA while maintaining zero-voltage switching (ZVS) throughout the grid cycle. Formal conditions for soft-switching and methods for achieving ZVS while maintaining global synchronization are presented. These conditions are then verified in a simulation. Finally, results for different power factors with and without interleaving are demonstrated in a prototype that achieves >98.1% efficiency when converting all real power.